From Policy to Implementation: The Role of Thai Universities in Developing Region Through Education Integration in ASEAN - Aroonpipat, Sunida (Thai Journal of East Asian Studies, 2018)
ASEAN has been publicly recognized that the state has played a leading role in developing the regional cooperation. With the dominated role of state in ASEAN, it has raised the question on the role of other actors apart from state that also pushes forth the cooperation at regional level. Therefore, the study on non-state actors helps understand not only the development of regional cooperation more comprehensively but also the phenomenon developed from the bottom (or non-state actors) which is believed to be the more sustainable path of regional cooperation by the scholar in the group of “regionalization”. This study focuses on the process of developing ASEAN from the bottom through the role of Thai universities. It shows that although the attempts of ASEAN and Thai government agency have institutionalized and formalized the education cooperation at regional level and national level, this has not yet stimulated the education cooperation from the bottom implemented by Thai universities due to the inconsistency of university’s ASEAN policy, the diverse directions of the university strategies, and ASEAN as a minor interest of Thai universities.